Fraud pentagon in detecting financial statement fraud - Arizanda Rahayu, Ruci; Nurasik; Arista Firana, Riza; Biduri, Sarwenda (Journal of Multiperspectives on Accounting Literature, 2024)
Purpose: This study aims to prove the influence of the fraud pentagon on the existence of fraudulent financial statements. Methodology/approach: This research approach is quantitative with secondary data in the form of company annual reports in the manufacturing sector with the food & beverage sub-sector listed on the IDX for the 2016-2020 period. Purposive sampling as sampling with a total of 12 companies for 5 periods and a total sample of 60. The analysis technique uses multiple linear regression assisted by SPSS 26. Findings: The findings prove that there is an influence of the variables of pressure, opportunity, rationalization, competence, and dualism position on financial statement fraud, while the variable frequent number of CEO's picture does not affect the existence of fraudulent financial statements. Practical implications: The findings of this study have an impact on the company's stakeholders and stake holders to detect fraud in the financial statements. Originality/value: This research has the novelty of adding a dualism position proxy variable to the arrogance element.